2018
DOI: 10.1097/sap.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

Low Versus High Vacuum Suction Drainage of the Submuscular Pocket in Primary Breast Reconstruction

Abstract: There is no significant difference in DDP and total drainage volume using low or high vacuum suction drainage in breast reconstruction. The only factors affecting drainage permanence were intraoperative filling of expander, smoking, and intraoperative bleeding. Therefore, we can reduce the DDP, avoiding overfilling of expander and using of high vacuum suction in nonsmoking patients and in patients with significant intraoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The most frequent complications in the surgical treatment of gynecomastia are hematomas and seromas, for this reason suction drains are placed and a compression chest garment is strictly recommended for at least one month after surgery [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complications in the surgical treatment of gynecomastia are hematomas and seromas, for this reason suction drains are placed and a compression chest garment is strictly recommended for at least one month after surgery [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis that the drain effect of the low vacuum drain was not inferior to the high vacuum drain after MRM or breast reconstruction was validated by our results. Several previous studies failed to address the drainage effect of different vacuum drain system after breast surgery due to defective design of clinical trials, which in turn resulted in limited clinical recommendations: 1) retrospective studies with absence of randomization, 10,14 2) small sample sizes, 10,14,17 3) baseline of these studies not taking the factors that might influence the drainage, eg, the nutritional state, 10,14,17 into account, and 4) using the total drain volume as a primary endpoint. 10,14 This study prospectively compared the effect of low and high vacuum drainage by using DDP as a primary endpoint, with a larger sample size and less confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results showed drain effect of the low vacuum drain were not inferior to the high one, which were in accordance with most previous results. 10,17 Chintamani et al 14 used the DDP as a primary endpoint and found that the half vacuum drains were removed earlier than the full vacuum drains (P<0.001). The results presented above indicate that the low vacuum drain has a similar drain effect compared to the high vacuum drain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations